2018
DOI: 10.1177/1076029618797465
|View full text |Cite
|
Sign up to set email alerts
|

Risk Assessment in Chinese Hospitalized Patients Comparing the Padua and Caprini Scoring Algorithms

Abstract: The current venous thromboembolism (VTE) guidelines recommend all patients to be assessed for the risk of VTE using risk assessment models (RAMs). The study was to evaluate the performance of the Caprini and Padua RAMs among Chinese hospitalized patients. We reviewed data from 189 patients with deep venous thrombosis (DVT) and 201 non-DVT patients. Deep venous thrombosis risk factors were obtained from all patients. The sensitivity and specificity of the Caprini and Padua scores for all patients were calculate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 35 publications
0
35
0
Order By: Relevance
“…This study also reported an overuse of pharmacologic thromboprophylaxis in this patient population without a significant increase in bleeding risk 39 . Another comparative study in a Chinese inpatient population showed that Padua and Caprini RAMs had a similar predictive value in cancer patients with Caprini having a higher predictive value in non-cancer patients 40 . Therefore, Caprini RAM can be appropriately utilized in medical oncology inpatients in the absence of better validated tools in this setting.…”
Section: Discussionmentioning
confidence: 97%
“…This study also reported an overuse of pharmacologic thromboprophylaxis in this patient population without a significant increase in bleeding risk 39 . Another comparative study in a Chinese inpatient population showed that Padua and Caprini RAMs had a similar predictive value in cancer patients with Caprini having a higher predictive value in non-cancer patients 40 . Therefore, Caprini RAM can be appropriately utilized in medical oncology inpatients in the absence of better validated tools in this setting.…”
Section: Discussionmentioning
confidence: 97%
“…Several studies are exploring the utility of the Caprini score in medically ill patients and those with cancer. 45,46 The Kucher model is an 8-factor weighted scoring system that uses computer alerts to identify high-risk populations (scores ≥4 points indicate high risk). In a randomized controlled trial, symptomatic VTE rates declined by 41% in high-risk patients after alerts were sent to providers.…”
Section: Risk Stratification Tools and Population Managementmentioning
confidence: 99%
“…The average AUC of Caprini was 0.7-0.8, Padua was 0.6-0.7 and Wells was 0.56-0.70 in previous study [24][25][26][27] . And in this study, the above RAM were all lower than 0.75, while the study results demonstrate that the AUC of the BP-ANN RAM was 0.828, which can signi cantly improve the productivity of LEDVT in critically ill patients.…”
Section: Discussionmentioning
confidence: 64%